A Life-Threatening Complication During the Fourth Pregnancy Due to Acute Promyelocytic Leukemia: A Case Report - Ismy Azizah Sisnawati; Kezia Salay; Listiana Nur Fadillah; Indi Jazilah; Jessica Amelinda Mintarjo; Atiyatum Billah; Agung Sunarko Putra; I Dewa Made Widi Hersana; Citra Novita (Acta Medica Indonesiana, 2024)
Incidents of leukemia in pregnancy are infrequent with only one case found from 75,000 to 100,000 pregnancies. The pathophysiological mechanism of leukemia during pregnancy is still unclear. Leukemia which occurs in pregnancy is usually acute and predominantly the myeloid type. A 35-year-old woman in her fourth pregnancy with a gestational age of 38-39 weeks, came to the emergency department (ED) with complaints of contractions since 4.5 hours before admission. The contraction was not accompanied by discharge, mucus, or blood, and fetal movements was still active. She denied complaints of fever, nausea, vomiting, dizziness, shortness of breath, weakness, fatigue, lethargy, and bleeding. Physical examination results, both palpebral conjunctiva were pale. Laboratory examination results of a complete blood count, white blood cell count were 2,930/uL, hemoglobin 8.3 g/dL, Hct 24.10%, erythrocytes 2.78x106/µL, platelets 62,000/µL. Bone Marrow Aspiration (BMA) revealed Acute Promyelocytic Leukemia (APL). APL is a subtype of Acute Myelogenous Leukemia (AML). Persistent fatigue, recurrent infections, and bleeding are common manifestations of APL. The diagnosis of APL is made by bone marrow aspiration examination, and it is safe for pregnancy. APL therapy in pregnancy uses All-Trans Retinoic Acid (ATRA) and Arsenic Trioxide (ATO). ATRA and ATO are highly teratogenic, but recent studies have reported no fetal abnormalities. Accuracy and speed in diagnosing and initiating APL therapy in pregnancy are essential in preventing serious complications.